Patterns and variation of seawater characteristics over Cambodian territorial Water - Sukchai Arnupapboon; Jitraporn Phaksopa (Agriculture and Natural Resources, 2007)
Horizontal and vertical distributions of salinity, temperature, and density (sigma-t) over Cambodian water at 11 stations in Cambodian water, were investigated during 18 - 26 November, 2005. The data were collected from 11 stations, covering the area from 09°15′ to 10°45′ N and 102°27′ to 103°30′ E. All the parameters were measured on board of the ship M.V. SEAFDEC2 using conductivity-temperature-depth sensor (CTD; SBE19). The results show that temperature was stable from surface to 15 - 20 m depth and rapidly increased by 0.5°C between the depth at 20 and 30 m. Temperature decreased again below this depth at all sampling stations, except at station 11 in the offshore area. The salinity and density profiles exhibit a similar pattern with stable values from surface to 15-20 m depth. The surface salinity was around 30.1 psu and surface density was 18.3 kg/m3. However, sudden changes in those parameters were observed in subsurface layer at 20 – 30 m water depth, below which they became stable again with salinity 33.7 - 33.8 psu and density 20.5 - 21.0 kg/m3. At nearshore station, due to river discharge, the salinity (29.8 psu) and density (18.3 kg/m3) were less than those of offshore station with salinity 30.5 psu and density 18.75 kg/m3. The results indicate that main factors influencing water characteristics during the survey period were river runoff, water intrusion and weak upwelling. In this period, Cambodian water can be separated into 2 layers. First layer is diluted water which covered from the surface down to the depth at 20-25 m with strong dilution near the Samit point. Subsurface layer approximately below 25 m is considered non-diluted water, affecting by the intrusion of water mass from South China Sea.